Gender Equality: Challenges toward Efforts to Minimize Child Marriage in Indonesia during the Covid-19 Pandemic - Judiasih, Sonny Dewi; Suryanti, Nyulistiowati; Sudaryat; Yuanitasari, Deviana (International Journal of Criminology and Sociology, 2021)
The practice of child marriage in Indonesia is a serious problem that must be resolved. This is a problem faced in various countries in the world. The SDG’s programs include achieving gender equality and empowering women and girls, with a target to achieve the abolition of child marriage by 2030. The research method used is a social-legal approach. The purpose of this study is to find out the government’s efforts in overcoming the problem of gender inequality in the age requirements for marriage in Indonesia and the application for dispensation for marriage during the Covid-19 pandemic in Indonesia. The old Marriage Law stipulates that the age of marriage for men is 19 years and for women 16 years. The government then changed this provision through Law Number 16 of 2019 concerning Marriage, in which the marriage age for men and women is the same, which is 19 years. During the Covid-19 pandemic, applications for marriage dispensation in Indonesia indicated a sharp increase. This means that the application for marriage dispensation is unaffected by the Covid-19 pandemic situation. The existence of exceptions through dispensation efforts makes the requirements for the age of marriage can still be deviated, so that gender equality, which is expected to minimize child marriages above, cannot be realized or cannot be carried out as desired.